Other infectious diarrhoeal disease incidence in Qinghai Plateau: temporal and spatial distribution during 2010 - 2020 - Jin-hua ZHAO; Bin-zhong MA; Jian-hai ZHAO (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo analyze spatial-temporal distribution characteristics and three-dimensional trend of other infectious diarrhoeal disease (OIDD) incidence in Qinghai Plateau - Qinghai province from 2010 to 2020. MethodsThe data on time (day, month, year)- and county/district-specific incidence of OIDD reported in Qinghai province during 2010 - 2020 were extracted from China Information System for Disease Control and Prevention. Visualization and three-dimensional analysis on average incidence of OIDD were performed with Arc GIS10.2 software and Scan 9.5 software was adopted in space-time scanning analysis. ResultsTwo seasonal incidence peaks of OIDD were observed with a major peak in autumn-winter season and a minor peak in summer during the period in the province. The OIDD incidence in male population was significantly higher than that in female population (χ2 = 1894.33, P < 0.001) and the average annual incidence was 897.26/100 000 for the children under 5 years old. Three-dimensional analysis showed that the OIDD incidence was higher in northeast region than that in the southwest region of the province. Spatio-temporal scanning analysis revealed major clusters of OIDD incidence in 4 counties/districts of Xining municipality and Haidong prefecture and minor clusters in 10 counties/districts of 5 prefectures. ConclusionIn Qinghai province during 2010 - 2020, the incidence of other infectious diarrhea diseases showed an increasing trend with a rising-unchanging-rising circle of every 2 - 3 years and the children under 2 years old were at a higher risk of the incidence.